OTOMASI PENJADWALAN LAPANGAN FUTSAL BERBASIS MIKROKONTROLER - , GALIH SUKMA PAWENANG, Esti Puspitaningrum, S.T., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
All the things of life are developed in line with the times. Technology is also growing and moving away from the conventional method becomes automatic. It is very closely associated with sports especially futsal that need automatic bell for every game of futsal. The automation scheduling of the futsal field is made to give an indication for starting the futsal game, for showing a 10 minute remaining before the futsal game end, and the end of the futsal game. The automation schedulingof the futsal fieldwork with the seven segments display, an 4x4 keypad for setting all parameters involved, and the loud AC220V buzzer as the warning time alarm. The time source is generated from a DS1307 RTC series, and the system is fully controlled by a microcontroller ATMega16. Preset of the time and date is needed before setting the alarm time of the futsal game. The alarm will buzz in accordance with the current time and alarm time setting is matched.